(untitled) (Research, Society and Development, 2021)
Several studies related to sociology and political sciences perceive the State as an important mechanism of social coercion. Analyzing the social development of humanity, it appears that the State has adapted to the different demands of the bourgeois elite, which holds power in the most diverse social and political contexts. With this capitalist transformation of society, there is also the subordination of social organization to the demands of capital. This is the moment when the construction of a state and political institutions takes place, both suited to the domination of the bourgeoisie. Given this context, this article aims to discuss the conceptual line that considers entrepreneurship as an alternative to the solution of a social and economic crisis. It is a qualitative and bibliographic research. For data collection, a theoretical survey was carried out in studies by Max Weber (1864-1920), Georg Wilhelm Friedrich Hegel (1770-1831) and Thomas Hobbes (1588-1651) in relation to the general theory of the State; Karl Marx (1818-1883) in relation to State intervention in economic and social aspects; and Schumpeter (1997), as it is an important reference in the study of entrepreneurship. The results contribute to the discussion on the concepts of entrepreneurship and the characteristics of entrepreneurs, in addition to addressing the process of entrepreneurship in a State marked by its historical subordination to capital. Thus, it is expected that the present study collaborates with the construction of the theoretical framework on entrepreneurship and innovation, in a more critical and contextualized perspective.